Countering the Australian ‘ndrangheta: the criminalisation of mafia behaviour in Australia between national and comparative criminal law - Sergi, Anna (The Australian and New Zealand journal of criminology, 2017)
Mafia-type criminal groups belonging to, or originated from, the Calabrian ‘ndrangheta from Southern Italy, have been object of recent academic research and media attention in Australia. The Australian ‘ndrangheta, as qualified form of organised crime, poses new challenges for law enforcement in the country. This paper briefly looks at the strategies to fight organised crime in Australia, with specific focus on anti-association laws. By using a comparative approach, the paper will look at the criminalisation of mafias as qualified forms of organised crime in other two jurisdictions, Italy and the USA, to advocate for an effective mafia criminalisation in Australia. In conclusion, this paper will argue that, in order to also fight mafia phenomena, criminal law in Australia should focus on behaviours of organised crime groups rather than only on the criminalisation of proscribed associations and their illegal activities.